THE IMPLEMENTATION OF SNOWBALL THROWING MODEL TO IMPROVE THE FIFTH-GRADE ELEMENTARY STUDENTS’ LEARNING OUTCOMES - Nela Rofisian; Putri Zudhah Ferryka (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the improvement of students’ learning outcomes through the implementation of the Snowball Throwing learning model. Snowball Throwing is a learning model that uses a sheet of paper and subsequently kneads it into a round shape resembling a ball, a question ball that is ready to be thrown to another student, and the students who have received the question ball must answer the question according to the allocated time. The research in this paper is Classroom Action Research, which is carried out in collaboration between the researchers and teachers. The research design is the Kemmis & Taggart model. Each cycle consists of the stages of planning, action, observation, and reflection. The research was conducted at SDN 1 Beluk with the subject of 18 fifth-grade students at SDN 1 Beluk, which consists of 11 female and 7 male students. Data collection techniques of the research include observation, learning outcome tests, and documentation. The research was conducted in two cycles, namely Cycle 1 and Cycle 2. In Cycle I, the average student score was 65.34 increased to 78.60 in Cycle II. The completeness of students’ learning outcomes increased from Cycle 1 at 66.6% of the number of students who completed the test and in Cycle II at 83.4% of the number of students who completed the test.